(untitled) (Journal of Environmental Science and Natural Resources, 2015)
Renewable energy presents a better alternative to fossil fuels with greener impact on environment. The present study was conducted to evaluate the opportunities and viabilities of using direct solar power as a source of green energy in irrigation to make the rice farming profitable one. In the present study 24 Polycrystalline of each 270 watt solar panels were installed in scattered manner at ?240 with a height of 7 ft. A D.C submersible pump of 3.5 KW was set up with a 90 ft depth deep-tubewell (DTW). In Bangladesh sunshine hour varies from 10 to 13 hours and solar radiation varies from 3.5 to 6.0 KW hm-2 day-1 through out year. By direct solar power, average running time of pump was 08 hours per day and full flow of water discharge was 4.5 hours per day. Average water discharge was 40710 liter per hour and total water discharge was 310 m3 per day. By the system a scheme of 15 acres of land was irrigated where 1.3 acre per day. The financial and economic value of BCR was 1.43 and 1.5, respectively; and the financial and economic value of IRR was 68% and 98%, respectively. J. Environ. Sci. & Natural Resources, 8(1): 125-128 2015